Attenuated total Reflectance–Fourier transform infrared (ATR–FTIR) spectroscopy coupled with chemometrics for rapid detection of argemone oil adulteration in mustard oil. (February 2020) - Jamwal, Rahul; Amit; Kumari, Shivani; Balan, Biji; Dhaulaniya, Amit S.; Kelly, Simon; Cannavan, Andrew; Singh, Dileep Kumar
Abstract: We have explored the feasibility of Attenuated total reflection- Fourier transform infrared (ATR-FTIR) spectroscopy coupled with multivariate chemometrics for the detection of Argemone oil (AO) adulteration in Mustard oil (MO). Twenty pure MO and one hundred forty MO adulterated samples with AO (1–30% v/v) were evaluated. From Principal Component Analysis (PCA), through spectral regions 3050-2750 cm −1 and 1800-500 cm −1, we observed well-defined discrimination of MO from AO adulterants. Linear Discriminant Analysis (LDA) was successfully applied to classify MO from AO. For quantification, Principal Component Regression (PCR) and Partial Least Square Regression (PLS-R) regression models were developed using combined optimized spectral regions (3050-2750 cm −1 and 1800-500 cm −1 ), and two separate optimized regions 3050-2750 cm −1 and 1800-500 cm −1 respectively for normal, 1st and 2nd derivatives. PLS-R model for 1st derivative spectral region of 1800–500 cm −1 showed best calibration model, with high precision and accuracy based on the values of Residual Predictive Deviation (RPD) of 52.23, Relative Prediction Error (RE %) of 0.033, Coefficient of Determination (R 2 ) of 0.999 and Root Mean Square Error of Prediction (RMSEP) of 0.2 v/v. The lowest detected percentage of AO in MO was the least adulteration level examined 1% v/v. Highlights: ATR-FTIR spectroscopy coupled with chemometrics methods was used to detect AO adulteration in MO. PCA and LDA models were developed to discriminate between AO and MO samples. Excellent R 2 (0.999), RMSEC (0.193) and RMSEP (0.20) values obtained for 1st derivative PLS-R. The detection limit of AO in MO by ATR-FTIR spectroscopy was 1% v/v. Present method is fast, non-destructive and requires no sample preparation.